2021
DOI: 10.1016/j.jpedsurg.2021.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultra high frequency ultrasonography to distinguish ganglionic from aganglionic bowel wall in Hirschsprung disease: A first report

Abstract: Background/Purpose: In Hirschsprung disease (HD) surgery, confirming ganglionic bowel is essential. A faster diagnostic method than the current frozen biopsy is desirable. This study investigated whether aganglionic and ganglionic intestinal wall can be distinguished from each other by ultra high frequency ultrasound (UHF ultrasound). Methods: In an HD center during 2019, intestinal walls of recto-sigmoid specimens from HD patients were examined ex vivo with a 70 MHz UHF ultrasound transducer. Data from four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Graneli et al 38 using 70 MHz‐UHFUS investigated children with Hirschsprung disease and concluded that UHFUS is a promising technique to identify aganglionosis, transition zones, and ganglionic bowel. Li et al 39 in a retrospective observational study, evaluated the characteristics of pilomatricoma in children and they concluded that 48 MHz‐UHFUS could be a useful tool for its diagnosis and evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Graneli et al 38 using 70 MHz‐UHFUS investigated children with Hirschsprung disease and concluded that UHFUS is a promising technique to identify aganglionosis, transition zones, and ganglionic bowel. Li et al 39 in a retrospective observational study, evaluated the characteristics of pilomatricoma in children and they concluded that 48 MHz‐UHFUS could be a useful tool for its diagnosis and evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Johnsson et al 30 ; Dangardt et al 31 ; Dangardt et al 32 ; Sarkola et al 33 ; Sundholm et al 34 Eklund et al 35 ; Jaberi et al 36 ; Kaufman et al 37 Evaluate parietal arterial thickness in patients with chronic renal disease, cardiovascular diseases, and after hand transplantation Granéli et al 38 Pediatric Evaluate aganglionosis, transition zones, and ganglionic bowel in Hirschsprung disease…”
Section: Clinical Evidence: Dermatological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common applications addresses difficult vascular access, with UHFUS being a promising tool in reducing vascular injuries related to peripheral arteries cannulation and central venous access [ 6 ]. Ultrasonography as a means of examining soft tissue was also explored by Granéli et al., whose hypothesis was that UHFUS could be used to differentiate aganglionic and ganglionic bowel wall during surgery for Hirschsprung Disease [ 7 ]. In fact, there is no other intraoperative method other than frozen biopsy to secure the level of ganglionic bowel.…”
Section: New Intra-operative Devicesmentioning
confidence: 99%
“…Technological innovations, such as fluorescence-guided surgery and augmented reality, are developing the broad field of image-guided surgery with the aid of more responsive and artificial intelligence enhanced robots [ 1 ], [ 2 ], [ 3 ]. In addition, innovative intra-operative imaging devices, such as intraoperative MRI, ultra-high frequency ultrasound, and photoacoustic imaging, are becoming crucial to give the surgeons novel tools for better field visualisation, anatomical prediction, and possible automated guidance [ 4 ], [ 5 ], [ 6 ], [ 7 ], [ 8 ], [ 9 ]. These novel imaging techniques and devices represent the future of surgery, and they are fast approaching clinical implementation.…”
Section: Introductionmentioning
confidence: 99%